Fluorogenic probes for detecting deacylase and demethylase activity towards post-translationally-modified lysine residues. Issue 7 (7th January 2021) - Hori, Yuichiro; Nishiura, Miyako; Tao, Tomomi; Baba, Reisuke; Bull, Steven D.; Kikuchi, Kazuya
Abstract : We developed "turn-on" fluorescent probes that detect enzymatic lysine deacylation and demethylation critical for epigenetic and other cellular phenomena, using intramolecular O - to N -ester transfer reactions. Abstract : Reversible enzymatic post-translational modification of the ε-amino groups of lysine residues ( e.g. N -acylation reactions) plays an important role in regulating the cellular activities of numerous proteins. This study describes how enzyme catalyzed N-deprotection of lysine residues of non-fluorescent peptide-coumarin probes can be used to generate N-deprotected peptides that undergo spontaneous O - to N -ester transfer reactions (uncatalyzed) to generate a highly fluorescent N -carbamoyl peptide. This enables detection of enzyme catalyzed N -deacetylation, N -demalonylation, N -desuccinylation and N -demethylation reactions activities towards the N-modified lysine residues of these probes using simple 'turn on' fluorescent assays.